The association between cerebrospinal ferritin and soluble triggering receptor expressed on myeloid cells 2 along Alzheimer's continuum - Shi, Xiaolei; Zhong, Xiaomei; Zhou, Huarong; Zhou, Nan; Hu, Yachun; Ning, Yuping; , Alzheimer's Disease Neuroimaging Initiative (Frontiers in Neurology, 2022)
Brain iron accumulation, which can be reflected by cerebrospinal fluid (CSF) ferritin, is associated with the development of Alzheimer’s Disease (AD). Studies have indicated that iron deposition might participate in Alzheimer’s pathology through the induction of microglial activation. Soluble triggering receptor expressed on myeloid cells 2 (sTrem2) in cerebrospinal fluid (CSF) is increasing recognized as a reliable indicator for microglia activity in brain, and participates in the development of neuroinflammation. However, the association between CSF ferritin and sTrem2 under the AD continuum has not been well established. We here enrolled individuals from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) database. Participants were classified into healthy controls (HC, n = 46) and AD continuum (n = 105) in the combined strata of ATN mode and CDR criteria. The associations between CSF ferritin (indicating iron burden) and sTrem2, as well as AD pathology, which reflected by Aβ42, tau and p-tau in CSF, were explored. CSF ferritin was significantly associated with sTrem2 among all participants (β = 0.517, P ＜0.001), HC (β = 0.749, P = 0.006) and AD continumm (β = 0.488, P ＜0.001), respectively. However, ferritin only predicted the accelerated sTrem2 level in those with high ferritin (β = 0.549, P = 0.036), but not in those with low ferritin (β = 0.131, P = 0.600). Moreover, ferritin in CSF indicated increasing tau in CSF in AD continuum (β = 0.179, P = 0.042). In conclusion, CSF ferritin could serve as a surrogate biomarker of Trem2-indicated microglia function.